A review of Scandinavian research on medieval church roofs - Robin Gullbrandsson (Tema, 2022)
The remarkable clusters of preserved high medieval church roofs in Scandinavia have been known since the early 20th century but surveys aimed at mapping and document these structures began first around 2000. The author reviews the State of Scandinavian research and presents recent and ongoing survey projects in Swedish dioceses. These cross-disciplinary projects have enhanced the value of historic timber structures as archaeological source material. A reading of craft techniques and tool marks provides insight into the work of the medieval carpenters. An example is presented of how a structured survey followed by moderate cleaning shaped a basis for maintenance and restoration in compliance with international principles.